Fall Composition of Storage Lipids is Associated with the Overwintering Strategy of Daphnia. Issue 1 (15th December 2016) - Mariash, Heather L.; Cusson, Mathieu; Rautio, Milla
Abstract: Diapause, which occurs through the production of dormant eggs, is a strategy used by some zooplankton to avoid winter months of persistent low temperatures and low food availability. However, reports of active zooplankton under the ice indicate that other strategies also exist. This study was aimed at evaluating whether the composition of storage lipids in the fall differs between diapausing and active overwintering Daphnia . We assessed the quantity of storage lipids and fatty acid (FA) composition of Daphnia species, along with FA content of seston, in six boreal, alpine and subarctic lakes at the onset of winter, and evaluated the association between storage lipids and Daphnia overwintering strategy. We found that active overwintering Daphnia had >55% body fat and the highest FA concentrations. Polyunsaturated FA, especially stearidonic acid (18:4n‐3; SDA) and high ratios of n‐3:n‐6, were preferentially retained to a greater extent in active overwintering Daphnia than in those that entered diapause. Daphnia FA composition was independent of that of the seston diet, indicating that Daphnia adjusted their storage lipids according to the physiological requirements of a given overwintering strategy. The occurrence of an active overwintering strategy has consequences for zooplankton community structure, and can have important implications for the transfer of high‐quality energy at higher trophic levels.